Identification Of Productive Landscape Potentials To Support The Eco-Pesantren Daar El-Qolam 3 Banten - Lola Rizka Amalia; Nur Intan Simangunsong; Rini Fitri (Journal of Synergy Landscape, 2023)
DAAR El-Qolam Islamic Boarding School, Tangerang Regency, Banten Province, has an area of ​​around 20 hectares. The development and arrangement of green open spaces is not good, the condition of open spaces in Islamic boarding schools is generally only grass fields and a few trees which are still wide. The DAAR El-Qolam Islamic Boarding School land has the potential to be developed and utilized for an eco-Islamic boarding school program in the form of a productive landscape. The purpose of this research is to identify the potential of green open space at Daar El-Qolam 3 boarding school as a productive landscape, to find out land use as a productive landscape that provides landscape elements, and to support aspects of agriculture, animal husbandry, fisheries and other productive businesses that can be used. as an educational medium at the Daar El-Qolam Islamic Boarding School 3. Data collection in this study used survey, interview, observation, and documentation methods. This research was conducted with a qualitative descriptive approach. The results of this study are expected to be a reference for the development of Islamic boarding schools Daar El-Qolam 3. Land use in open space areas as productive landscapes can optimize the function of land use for agriculture, animal husbandry, fisheries and productive businesses.